EFFECT OF ANTIOXIDANT SUPPLEMENTATION IN DIETS OF ROOSTERS DURING THE POST-PEAK PHASE ON REPRODUCTION AND PRODUCTION CHARACTERISTICS OF OFFSPRING - Gustavo Eugenio Triques; Adrieli Braga De Cristo; Murício Canevese; Patricia Fernanda dos Santos Marques; Jovanir Ines MUller Fernandes; Alvaro Mario Burin Junior (Ciência Animal Brasileira, 2019)
This study aimed to evaluate the effects of antioxidant supplementation in diets of breeding roosters during the post-peak phase on reproduction characteristics and muscle performance of offspring in two similar breeder houses from a local company. Treatments consisted of a control diet and a diet supplemented with antioxidants (8 ppm canthaxanthin + 40 ppm lycopene + 150 ppm vitamin C). During the 66th week of age, eggs were incubated, and offspring were housed. Dietary supplementation of the blend of antioxidant resulted in higher (p<0.05) weights of testicles, crests, dewlaps, dewlap thickness, and number of perforations (53.35 x 25.30) in relation to non-supplemented roosters. There was no significant effect (p>0.05) of supplementation of the antioxidant blend on weight gain and breast weight and count and diameter of muscle fibers of offspring at 7 days of age. Feed conversion and weight gain from 14 to 35 days were better (p<0.05) in offspring from supplemented roosters. The supplementation of an antioxidant blend in roosters improved reproductive characteristics assessed and feed conversion and weight gain of offspring. Keywords: antioxidant; lipid peroxidation; plasmatic membrane of sperm; muscle fibers; perivitelline membrane